Factors Influencing University Students’ Consumption Behavior Towards McDonald’s: The Roles of Media Advertisement, Menu Innovation, and Brand Image - Yee Huei Lok; Guo Hao Eu; YuTong Ding; Tan Doann; Farah Aqilah Ibrahim; Reet Saxena; Mitali Khandelwal; Daisy Mui Hung Kee (AIBPM Publisher, 2026)
In the highly competitive fast-food industry, understanding university students’ consumption behavior is critical for McDonald’s to maintain market share. This study examines the role of media advertisement, menu innovation and brand image that is influencing university students’ consumption behavior towards McDonald’s. A quantitative research design was employed. Data were collected from 150 university students using an online survey distributed via Google Form to test the proposed hypotheses. Our findings reveal that media advertisement, menu innovation and brand image positively influence university students’ consumption behavior toward McDonald’s. Furthermore, it contributes to both theoretical and practical insights by demonstrating that improving media advertisement, menu innovation and brand image can enhance the consumer consumption behavior among university students